A Symbolic Image of Depression in Lars von Trier’s Melancholy - Kowalski, Hanna (Media - Culture - Social Communication, 2021)
The author of this article systematizes reflections on the problems of depression and melancholy and the resulting trauma based on the example of Melancholy directed by Lars von Trier. She analyses and interprets the symbolism of depression contained in the film. In the article, it is shown that the image of depression presented in Melancholy rises to the rank of a symbol that portrays different social attitudes towards illness and has a communicative function towards the viewer. These analyses involve research on the anthropology of the image, as well as the analysis of the symbolic language, which is important, among other things, in the consideration of the nature of broadly understood social experiences.